Always Best Connected Mobile Sensor Network to Support High Accuracy Internet of Farming - Ahmed H. Alahmadi (Computer Engineering and Applications Journal, 2017)
The Internet of Farming be dependent on data gathered from sensor of Wireless Sensor Network (WSN). The WSN requires a reliable connectivity to provide accurate prediction data of the farming system. This paper introduces a mechanism that gives always best connectivity (ABC). The mechanism considers all stakeholders (mobile node, corresponding node and users) attributes. An empirical simulation shows that the proposed mechanism provides an acceptable ABC to the mobile sensors in the WSN.